Characterization of natural peanut butter produced by one-stage fine grinding method using ultra-high speed grinder - Mohd Rozalli, Norazatul Hanim (2015)
Peanut butter is a major product of peanuts (Arachis hypogaea L.) consumed worldwide. The concerns with additives in food products attract the demands for alternative natural peanut butter in market. It is common in peanut butter production that two stages of size reduction are required to transform the peanuts into paste form. Little attempts had been made to minimize the grinding stage and producing natural peanut butter as well. This study focuses on producing natural peanut butter by single 1-stage fine grinding method using ultra-high speed grinder. An extensive study on interrelation of particle size and natural peanut butter properties were conducted. Comparisons were made with commercial peanut butter in quality aspects. The qualities of roasted peanuts were optimized in roasting process. The effect of hot-air roasting temperatures and time on quality attributes of two different types of peanuts (Virginia and Spanish variety) were investigated using response surface methodology (RSM). The optimum roasting parameters for the Virginia and Spanish peanuts was 152°C-60 minutes and 158°C-45 minutes, respectively. Roasted peanuts were ground in a commercial ultra-high speed grinder operated at 20000 rpm for 2.0-5.0 minutes for natural peanut butter production. Grinding characteristics of both peanuts were evaluated in terms of specific energy consumption, Esc with respect to its grinding time and mean particle size. The specific energy consumption modeled to the size reduction ratio of Virgina and Spanish peanuts was predicted more accurately using a linear and exponential model respectively compared to the classical models by Bond, Rittinger and Kick. Bond’s working index, Wi, the ultra-high speed grinder is said to be more energy efficient than other comminutors in terms of its capability to produce finer particle size in shorter time than the rest. The peanut butter was successfully produced by 1-stage fine grinding method using the ultra-high speed grinder. Particle size analysis of natural peanut butter exhibited statistically significant difference between the analyzed parameters (d0.1, d0.5, d0.9). Multimodal particle size distribution (PSD) was observed for all the samples. Particle size distribution is an inverse function of grinding time. All peanut butter samples exhibited elastic properties, adequately fitted to the Casson model and behaved as non-Newtonian shear-thinning food suspension with apparent yield stress. The storage modulus (G′) is a decreasing function of grinding time and temperature. Grinding time and temperature show significant effect on all the responses (p≤0.05) while peanut origins only had impact on the particle size distribution. Identical trend was observed on all tests between natural peanut butter of Virginia and Spanish peanuts. The storage stability of natural peanut butter was evaluated for changes in physicochemical quality, microbiological properties, oxidative stability and textural quality. For storage study conducted over 16 weeks at 10, 25 and 35°C, products stored at 10°C exhibited similar textural quality with commercial product without appreciable loss in oxidative stability until the 12th whereas it was within 4 weeks for 25°C and 35°C storage. Storage temperature and time have more significant impact than other factors on quality changes of natural peanut butter during storage.